An Analysis of Illocutionary Acts of The Main Character in The Little Mermaid (2023) Movie (English Language and Literature (JELL), 2026)
This study aims to analyze the types of illocutionary acts used by the main characters in The Little Mermaid (2023) Movie. Speech acts are divided into three types: locutionary acts, illocutionary acts, and perlocutionary acts. In this study, illocutionary acts are the main focus because they represent the speaker’s intention in an utterance. The researcher used a qualitative descriptive method for this research. This study applied Kreidler’s theory (1998) to analyze the types of illocutionary acts. The subjects of this study are the main characters (Ariel, Eric, and Ursula) in The Little Mermaid (2023), and the object of the study is the utterances containing illocutionary acts in the movie script. The findings reveal six types of illocutionary acts used by the main characters, including assertive 175 (48.61%) data, verdictive 11 (3.06%) data, expressive 59 (16.94%) data, directive 61 (16.94%) data, commissive 18 (5.00%) data, and phatic 36 (10.00%) data. Among these types, assertive is the most dominant, with 175 (48.61%) utterances.
Keywords: speech acts; illocutionary acts; lingustics